2018
DOI: 10.3762/bjnano.9.202
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun one-dimensional nanostructures: a new horizon for gas sensing materials

Abstract: Electrospun one-dimensional (1D) nanostructures are rapidly emerging as key enabling components in gas sensing due to their unique electrical, optical, magnetic, thermal, mechanical and chemical properties. 1D nanostructures have found applications in numerous areas, including healthcare, energy storage, biotechnology, environmental monitoring, and defence/security. Their enhanced specific surface area, superior mechanical properties, nanoporosity and improved surface characteristics (in particular, uniformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 299 publications
0
39
0
1
Order By: Relevance
“…Detection systems for various chemical, physical, environmental, and biological targets, so-called sensors, have been continuously explored [14]. Although their usefulness was recognized even in the early stages of modern science and technology, the importance of sensors has been recently re-evaluated in the context of current research developments.…”
Section: Introductionmentioning
confidence: 99%
“…Detection systems for various chemical, physical, environmental, and biological targets, so-called sensors, have been continuously explored [14]. Although their usefulness was recognized even in the early stages of modern science and technology, the importance of sensors has been recently re-evaluated in the context of current research developments.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier in [15][16][17][18][19][20][21][22][23], it was shown that one of the most promising fields of application of metal oxide 1D nanomaterials is the development of conductometric gas sensors based on them. As it is followed from discussions presented in Part 1 of our article [24], metal oxide nanofibers are also a promising material for these applications, since a nanofiber mat, forming a gas-sensitive layer, is characterized by high porosity and a large surfaceto-volume ratio [12,25,26]. In addition, the metal oxide crystallites in nanofibers can have an extremely small size [27].…”
Section: Introductionmentioning
confidence: 91%
“…As it was indicated before, nanofibers are not 1D structures, in the classical understanding, as metal oxide nanowires or nanobelts and nanotubes. However, research has shown that the features of the nanofiber configuration and the size factor play a positive role in the development of gas sensors based on nanofibers [12,26,[65][66][67][68][69][70][71]. As mentioned above, metal oxide nanofibers, which usually have a diameter in the range of 50-1000 nm and a length from several micrometers to centimeters and meters, have many unique properties of gas-sensitive materials, such as a very large surface area per unit mass, high porosity and a small size of crystallites that form nanofibers.…”
Section: Fabrication Of Gas Sensors Based On Metal Oxide Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also applicable as nanosized analogs of metallic conductors of macroscopic instruments. Large surface area maintains an interest in such materials in gas sensing 3 and liquids analysis 4 . Among variety of such materials, emeraldine, a semi-oxidized form of polyaniline, is most attractive due to easy preparation, low toxicity and low electric resistance 5 .…”
Section: Introductionmentioning
confidence: 99%